Drug trafficking in the Golden Triangle - Zhang, Sheldon (Henry Stewart Talks, 2008)
The Golden Triangle as a breadbasket of heroin and amphetamine type drugs, Major political changes in recent decades, Shifts in trafficking routes and rise of China's drug addicts, Emergence of entrepreneurs in drug trafficking business, Fragmentation of drug trafficking and distribution in China and Southeast Asia
Archived at 2022/04/03